The Interplay of Climate Change, Urbanisation, and Species Traits Shapes European Butterfly Population Trends - Pau Colom; Ashley Tejeda; Simona Bonelli; Benoît Fontaine; Mikko Kuussaari; Dirk Maes; Xavier Mestdagh; Miguel L. Munguira; Martin Musche; Lars B. Pettersson; David Roy; Johannes Rüdisser; et al. (Global Ecology and Biogeography, 2026)
Aim To examine how butterfly population trends respond to climate change and urbanisation at a continental scale, and whether responses differ between urban and rural environments. Location 869 sites across 12 European countries, spanning six bioclimatic zones. Time Period 1976–2021. Major Taxa Studied Butterflies (Lepidoptera). Methods We analysed long‐term monitoring data from > 8400 populations of 145 species representing a wide range of ecological and life‐history traits. Population trends were modelled in relation to climate variables (temperature, precipitation and aridity), urbanisation (built‐up surface), and their interactions with urban context (urban vs. rural) and species traits (trophic specialisation, body size, reproductive rate and thermal adaptation). Results Climate warming and aridification were consistently linked to population declines in both rural and urban contexts, while precipitation effects varied by location and species. Urbanisation alone did not predict trends, but the urban–rural context strongly modulated species' responses to warming, indicating potential synergies between climate change and urbanisation. The stronger impact of warming in urban populations likely reflects elevated baseline temperatures and reduced habitat suitability and connectivity in urban landscapes, limiting thermal buffering. Species with colder thermal niches and lower reproductive rates were most vulnerable to warming, as warming exceeds the thermal optima of cold‐adapted species and lower reproductive rates limit their capacity to buffer climate‐driven population declines. Under aridification, which can reduce host‐plant availability, trophic specialists declined more in urban areas, whereas generalists unexpectedly declined more in rural sites, suggesting context‐dependent constraints under increasing water limitation. Main Conclusions Our findings highlight the complex interplay between climate change, urban context, and species traits in driving population dynamics. Importantly, our results suggest that urbanisation generally amplifies the negative impact of climate change on insect population trends.